PENERAPAN PELAYANAN EMERGENCY SAVERITY INDEX DI IGD RSUD H PADJONGA DG.NGALLE KABUPATEN TAKALAR - Sahrawati, Sahrawati; Tahir, Muhammad; Abdi, Abdi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2023)
The main problem in this study was how the quality of the implementation of the emergency saverity index service in the emergency room at RSUD H.padjonga Dg.Ngalle, Takalar Regency. This study used descriptive qualitative research methods. Data collection techniques used observation, interviews and documentation. Research informants were 3 people. Validation of data through triangulation of sources, techniques and time, then analyzed through data reduction, data presentation and conclusions. The results showed that the indicators 1) Service accuracy. 2) Timeliness of service. 3) Responsibility. 4) convenience in service. 5) Equipment. 6) As well as politeness and friendliness, everything was in the good and quality category. It seen from serving and treating patients based on Standard operating procedure's, fast respon in serving patients, guarantees for patient safety and security, clear service flow, and serving with the 5S principle, but communication techniques with patients' families still need to be improved. And the punctuality of service still needs to be improved. Humanity should not discriminate between patients based on their illness.